The Influence of Product Quality, Price Discounts, and Promotions on Purchasing Decisions at the Musafir Fashion Store in Pasar Raya, Banjar Regency - Audah, Ali; Kadir, Abdul; Naimah, Naimah; Jahra, Pati Mutu; Badrian, Badrian; Syarqawie, Fithriana (Universitas Hang Tuah, 2026)
This study aims to analyze the effect of product quality, price discounts, and promotion on purchasing decisions at Musafir Fashion Store, Pasar Raya Martapura, Banjar Regency. This research employed a quantitative approach using a survey method. The population consisted of consumers who made purchases at the store, with a sample of 68 respondents determined using the Lemeshow formula. Data were collected through questionnaires, and data analysis techniques included multiple linear regression analysis, validity test, reliability test, F-test, t-test, and standardized beta coefficient test. The results indicate that product quality, price discounts, and promotion simultaneously have a positive and significant effect on purchasing decisions. Partially, each variable—product quality, price discounts, and promotion—also shows a positive and significant effect on purchasing decisions. Based on the dominance test, price discount is the most influential variable affecting purchasing decisions compared to product quality and promotion. These findings suggest that an appropriate price discount strategy, supported by good product quality and effective promotional activities, can significantly enhance consumer purchasing decisions.